2012
DOI: 10.1017/s0033291712001535
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological evidence for abnormal neurodevelopment associated with early-onset psychoses

Abstract: Cognitive impairment in EOP is already present at the first episode, and cognitive development seems to be arrested early in EOP patients compared to their healthy peers, at least for some cognitive functions. These and previous similar results support the neurodevelopmental hypothesis of psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 48 publications
(62 reference statements)
7
46
0
1
Order By: Relevance
“…52 In line with the possibility that patients with psychosis have a particularly degenerative or deteriorating outcome, first-episode early-onset psychosis patients have been shown to have low antioxidant status, with no differences between schizophrenia and bipolar patients; however only those with schizophrenia have lower glutathione at baseline. 74 In terms of cognition, the impairment seems to remain similar during the first 2 years after the first psychotic episode in bipolar and schizophrenia patients, 23 with cognitive reserve (composed of an estimation of premorbid IQ and a measure of educational-occupational levels and lifetime leisure-social activities) predicting long-term working memory and attention.…”
Section: What Happens After a First Psychotic Episode In Children Andmentioning
confidence: 98%
See 1 more Smart Citation
“…52 In line with the possibility that patients with psychosis have a particularly degenerative or deteriorating outcome, first-episode early-onset psychosis patients have been shown to have low antioxidant status, with no differences between schizophrenia and bipolar patients; however only those with schizophrenia have lower glutathione at baseline. 74 In terms of cognition, the impairment seems to remain similar during the first 2 years after the first psychotic episode in bipolar and schizophrenia patients, 23 with cognitive reserve (composed of an estimation of premorbid IQ and a measure of educational-occupational levels and lifetime leisure-social activities) predicting long-term working memory and attention.…”
Section: What Happens After a First Psychotic Episode In Children Andmentioning
confidence: 98%
“…23,24 The discrepancy between the data showing cognitive impairment in bipolar disorder and close relatives [25][26][27][28] and the better premorbid cognitive functioning and scholastic performance in longitudinal studies in subjects who end up having adult bipolar disorder could be due to sample selection bias, medication, drug use, cognitive decline prior to the first psychotic episode, or other confounding factors. Reading difficulties and scholastic underachievement, however, seem to be more specific to early-onset schizophrenia than early-onset bipolar I disorder.…”
Section: Cognitive Impairment During Development In Schizophrenia Andmentioning
confidence: 99%
“…Two studies on late-onset BD did not find a relationship between cognitive decline, severity of symptoms, and duration illness [36,37]. Other studies concluded that there was little to no evidence that deficits in cognitive domains such as psychomotor speed, verbal memory, and executive functions were associated with markers of illness progression in BD [38][39][40][41][42][43][44][45].…”
Section: Cognitive Decline In Bipolar Disordermentioning
confidence: 99%
“…Therefore, some authors suggested that severe mood symptoms could act like stress-induced neurotoxins (Lopez-Jaramillo et al, 2010). In contrast, other studies found that first-episode BP patients have the same neurocognitive performance as patients with multiple episodes in the past (Bombin et al, 2013;Hellvin et al, 2012). Torrent et al (2012) described in a recently published longitudinal study that cognitive impairments (except for a worsening of executive functions) remained stable over nine years, irrespective of severe relapses in the meantime.…”
Section: Introductionmentioning
confidence: 99%